Study of Soil Infiltration in Various Fields in Durin Tonggal Village Experimental Plots Pancur Batu Subdistrict Deli Serdang District - Andrean Hendratmo Hutabarat; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2015)
Infiltration is one of very important element in the hydrological cycle as it relates to the intensity of rainfall that will affect the water storage in the soil and erosion. This study was aimed to determine the rate of infiltration in the fields of rubber, cassava, maize and cacao in subdistrict Pancur Batu using Philips equation model. The results showed that in the field of rubber with argillaceous sand texture the infiltration rate was fp = 0.460006 + 2,24274t-0,5 cm / min, in the cassava fields with sandy loam texture the infiltration rate was fp = 0.018388 + 2 , 40156t-0,5 cm / min, in maize field with sandy clay loam soil texture the infiltration rate was fp = 0.08988 + 1,95682t-0,5 cm / min, and cacao field with sandy clay loam texture the infiltration rate was fp = 0.05513 + 0,44371t -0,5cm / min. Keywords: Cacao Field, Cassava Field, Infiltration rate, Maize Field, Rubber Field